DESIGNING CONTEMPORARY ART GALLERY WITH METAPHORE ARCHITECTURE APPROACH IN MEDAN CITY - Rajagukguk, Rotua; Ginting, Nurlisa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
This study explores the application of the Metaphorical Architecture approach in the design of Contemporary Art Galleries, with a focus on its benefits and impact on art interaction and visitor experience. Art is defined as the expression of ideas, emotions, and the turmoil of the soul through aesthetic elements to fulfill human needs. Art galleries serve as platforms for artists to exhibit, store, and promote their artworks to the public, while also functioning as spaces for education and entertainment. Contemporary art galleries, in particular, are edutainment spaces that present modern art in interactive and engaging ways.Metaphorical architecture, as a design strategy, employs symbolism to convey deeper meanings, enhancing both the visual appeal and aesthetic value of a building. Indonesia, despite its rich artistic heritage, faces challenges in providing adequate art facilities, especially in cities such as Medan. This research was conducted using a qualitative method through literature review and comparative object analysis to identify and apply metaphorical elements in architectural gallery design.The findings indicate that the metaphorical approach enables the creation of buildings that transcend mere physical space, enriching the interaction between architecture and art, and enhancing the aesthetic experience of visitors. Contemporary galleries designed with this approach function not only as exhibition venues but also as works of art themselves, enabling broader creative exploration in contemporary architectural design.Therefore, this study affirms that the application of metaphorical architecture in contemporary art galleries can significantly enrich visitor experiences and support the advancement of modern art in Indonesia